INDIA’S INTERESTS IN AFGHANISTAN SINCE 9/11 - Ganie, Subdar Ahmad (International Journal For Research In Business, Management And Accounting, 2018)
The paper will analyse the India‟s interests in Afghanistan since 9/11. India is working for a stable, secure and prosperous neighbourhood and Afghanistan is a road for such design. Afghanistan holds the political and economic significance for India. The country is helping Afghanistan to preserve security and strengthening strategic- partnership, but it faces the problems from others like, Pakistan who does not want to see the good and stable relations between the two. Since 9/11 Afghanistan‟s Foreign Policy towards New Delhi is quite receptive. India‟s activities in Afghanistan had a geo- strategic flavour though, which not only confine to Afghanistan but travel deep into Central Asia. It is now widely accepted that India‟s afghan policy seeks access to energy resources of the region, and elimination of anti Indian terrorism.